Follow-up conditions of care and associated factors among adult hypertensive patients during COVID-19 at West Arsi public health facilities, Southeastern Ethiopia: A multi-center cross-sectional study - Hiko, Ahmed; Assefa, Nega; Ataro, Zerihun; Sertsu, Addisu; Yadeta, Elias; Balcha, Teganu; Amano, Abdulkerim; Asfaw, Henock; Dechasa, Deribe Bekele; Nigussie, Kabtamu; Abdisa, Lemesa (Frontiers in Public Health, 2022)
Background Coronavirus disease (COVID-19) is a viral-borne infection caused by the SARS-CoV-2 virus. Aside from the morbidity and mortality effects, it leaves the majority of hypertensive patients untreated and vulnerable to uncontrolled hypertension. Objective The purpose of this study was to assess follow-up conditions of care and its associated factors among adult hypertensive patients during COVID-19 in public health facilities of West Arsi, Southeastern Ethiopia. Methods A health facility-based retrospective cross-sectional study was conducted among 423 adult hypertensive patients in the West Arsi public health facilities from July 5 to August 6, 2021. A systematic random sampling technique was used to recruit the study participants. A pretested structured face-to-face interviewer and medical records were used to collect sociodemographic variables, basic clinical features, and follow-up data. The follow-up conditions of care were assessed using 12 items with “yes or no” questions. Then, based on the mean value of the items, the follow-up conditions of care were dichotomized into good and poor. As a result, the follow-up condition was good if the score was greater or equal to the mean, and poor unless otherwise. To investigate parameters related with follow-up conditions of care, bivariable and multivariable logistic regression analyses were used. A 95% confidence interval and a p-value of 0.05 were used to indicate a significant association. Results The rate of poor follow-up conditions of care during COVID-19 was 29% (95% confidence interval: 24.9–33.4%), according to this study. Age ≥ 60 years (AOR = 3.55; 95% CI: 2.09–6.03), transportation problem (AOR = 2.43; 95% CI: 1.28–4.61), fear of COVID-19 (AOR = 3.34; 95% CI: 1.59–7.01), co-morbidity (AOR = 1.93; 95% CI: 1.14–3.26) and physical distancing (AOR = 2.43; 95% CI: 1.44–4.12) were significantly associated with poor follow-up conditions of care. Conclusions In our study, 29% of the participants had poor follow-up care conditions. When compared to WHO recommendations, the findings of this study may explain poor follow-up care conditions. To enhance patients' follow-up treatment, evidence-based target interventions should be designed and executed, taking into account individuals at high risks, such as those over the age of 60 and those with comorbidities, and identifying additional risk factors.